All‐Solid‐State Organic Schmitt Trigger Implemented by Twin Two‐in‐One Ferroelectric Memory Transistors. (20th March 2020) - Hwang, Sunbin; Jang, Sukjae; Bae, Sukang; Lee, Seoung‐Ki; Lee, Sang Hyun; Fabiano, Simone; Berggren, Magnus; Lee, Takhee; Kim, Tae‐Wook
Abstract: Although there have been many attempts to replace conventional inorganic electronics with organic materials that can be mass produced at low cost, few organic electronic filters to increase immunity to electrical noise have been reported thus far. Conventional Schmitt triggers or their inverters are used in many electronic circuits as versatile electronic noise filters. However, it is challenging to manufacture organic electronic systems with complex circuitry. In this study, a simple, all‐solid‐state organic Schmitt trigger consisting of twin two‐in‐one organic ferroelectric memory transistors with the same chemical compositions and device dimensions but different threshold voltages is introduced. Threshold voltages and hysteresis in the two‐in‐one devices can be controlled by polarization switching as demonstrated in a previous study. Hysteresis of a ferroelectric p‐type depletion load inverter can be achieved using twin two‐in‐one devices when the sweep voltage is higher than the critical gate voltages. This facilitates inverter characteristics at two different threshold voltages, and realizing a Schmitt trigger. Finally, based on simulation program with integrated circuit emphasis (SPICE) simulation, guidelines are proposed on how to design organic Schmitt triggers with p‐ or n‐type materials and ferroelectric or charge‐trapping mechanisms to achieve inverting or non‐inverting characteristics. Abstract : A simple all‐solid‐state organic Schmitt trigger consisting of twin two‐in‐one organic ferroelectric memory transistors with pentacene as the channel and photocrosslinked poly(vinylidene fluoride‐trifluoroethylene) as the dielectric layer is presented. The output behavior of this Schmitt triggers in response to various input signals (square, triangle, sine and sine with 8 V random noise) is investigated.